2014
DOI: 10.1371/journal.pone.0100146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Spectrum of Autosomal Recessive Non-Syndromic Hearing Loss in Pakistani Families

Abstract: The frequency of inherited bilateral autosomal recessive non-syndromic hearing loss (ARNSHL) in Pakistan is 1.6/1000 individuals. More than 50% of the families carry mutations in GJB2 while mutations in MYO15A account for about 5% of recessive deafness. In the present study a cohort of 30 ARNSHL families was initially screened for mutations in GJB2 and MYO15A. Homozygosity mapping was performed by employing whole genome single nucleotide polymorphism (SNP) genotyping in the families that did not carry mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 51 publications
2
44
1
Order By: Relevance
“…A total of six different mutations were identified in the study, with W24X as the major mutation found, followed surprisingly by c.35delG being the second most prevalent, surpassing Q124X, W77X, V153I, and T8M. Furthermore, sequence analysis of GJB2 in 30 consanguineous families with NSHL from different regions of Punjab, by Shafique et al (2014), revealed the presence of mutations in this gene in 16 families (53%). W24X and W77X were the most common mutations found.…”
Section: Dfnb1/gjb2mentioning
confidence: 94%
See 2 more Smart Citations
“…A total of six different mutations were identified in the study, with W24X as the major mutation found, followed surprisingly by c.35delG being the second most prevalent, surpassing Q124X, W77X, V153I, and T8M. Furthermore, sequence analysis of GJB2 in 30 consanguineous families with NSHL from different regions of Punjab, by Shafique et al (2014), revealed the presence of mutations in this gene in 16 families (53%). W24X and W77X were the most common mutations found.…”
Section: Dfnb1/gjb2mentioning
confidence: 94%
“…These seventeen missense, nonsense, and splice site mutations are located in exons encoding motor and first FERM domains of MYO15A. In a more recent study, 4/30 (13%) families were found to have mutation in MYO15A (Shafique et al, 2014). These include four unreported variants, of which two were splice site mutations (c.9948G > A and c.3866 + 1G > A), one was a nonsense (p.R2923X), and one missense mutation (p. F2741S).…”
Section: Dfnb3/myo15amentioning
confidence: 98%
See 1 more Smart Citation
“…Homozygosity mapping was subsequently performed in families W06-0987, W09-1575 and W09-1600 as part of a larger project directed toward the identification of genetic defects underlying sensorineural HI in consanguineous Pakistani families and nonconsanguineous families of The Netherlands. 27,30 In the only affected individual II.3 of family W06-0987, homozygosity mapping revealed nine homozygous regions larger than 1 Mb (Table 1). The second large homozygous region harbored TRIOBP, the gene associated with the known arNSHI type DFNB28.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…Mutations in GJB2 account for 6.9% (95%confidence interval, 3.2–10.4%), of moderate to profound deafness in Pakistanis living in the UK, as inferred from analyses of samples from 123 sib pairs [8]. However, the contribution of GJB2 mutations to deafness in Pakistan was reported to be as high as 53%, (95% confidence interval, 35–71%), in a study involving 30 families with severe to profound deafness [9]. The large discrepancy between the results of this research on 30 families and the estimates of frequency of mutations in GJB2 obtained from previous studies is not clear, although small sample size of these studies may have contributed to the difference.…”
Section: Introductionmentioning
confidence: 99%